Systemic Analysis of Gender-Responsive Planning and Budgeting Policies in Kulon Progo Regency - Nuryati, Akhid; Yuliadi, Imamudin; Ma’ruf, Ahmad (Dinasti Publisher, 2026)
This study examines the structural dynamics of gender-responsive planning and budgeting (GRPB) implementation at the local government level in Kulon Progo Regency, Indonesia. Using a qualitative exploratory design, the research applies MICMAC structural analysis to identify and classify the key indicators shaping GRPB implementation. Data were collected through a literature review, regulatory analysis, and structured stakeholder assessments involving planning agencies, sectoral offices, and gender focal points. The analysis maps direct and indirect influence–dependence relationships to understand the systemic structure of gender-responsive governance. The findings indicate that the regulatory environment, policy consistency, and leadership commitment function as the primary driving factors determining the direction and stability of GRPB implementation. Institutional capacity, women’s participation, economic policy orientation, and inter-organizational coordination act as linkage factors that transmit influence throughout the system, while the integration of gender perspectives into planning and budgeting, together with monitoring and evaluation mechanisms, represents outcome indicators shaped by broader institutional dynamics. These results suggest that effective GRPB implementation depends more on strong institutional coherence than on isolated technical actions. Although the study is limited to a single district and relies on stakeholder perceptions, it offers a systemic framework for strengthening institutional governance in gender-responsive fiscal policy. By adopting a systems-based perspective, this research contributes to the literature on subnational gender budgeting and provides insights for improving the institutional design of gender-responsive governance.